The Enhancement of The Surface Properties of 316, 304 Stainless Steel by Coating ZnO Films by PLD Method - Sarah A. Jasim; Ammar A. Habeeb; A. Kadhim (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2023)
This study employed two alloys of AISI (316,304) Stainless steel to improve the mechanical characteristics. In addition, the corrosion rate achieved by pulse laser deposition (PLD) can be reduced by applying a ZnO coating. Zinc oxide has garnered significant interest. Biomaterials have long been well-acknowledged for their use in dentistry and medical applications. Using an optical microscope examined the coating morphology, scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS). The corrosion protection has been examined by assessing the mechanical characteristics when submerged in saliva with a pH of 5.6. The surface alteration is assessed using roughness and microhardness measurements. The corrosion resistance of all samples is superior to that of bare AISI (316,304) stainless steel.